(3GdWQGR aj Ydhe GdMbGFb GdEYLGRs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdHGH GdKGdK ai eQGYGI CMhGd GdJCdja hHjGf XghQ GdeYGfi GdeQcHI s
(3BNQgG (B:s
(3hhabfG dEMQGR QVhGfc GdCSei hcGf GdaQGZ ef JCdjag SfI KeGfi hYTQjf hSHYeGFI s
(3GdfSNI HgG MhGTs
(3Ydi MhGTi GdfSNI JYdjbGJ LjOIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO RHGQI GdNGUI HUfYGA (B((3HdGZI (B8) s
Keywords: (3GdHdGZIs